A study in cellular manufacturing using production flow anylysis (PFA) simulation technique - Suberamaniam, K. (2000)
In current manufacturing industry, competitiveness is high in producing components in a shorter period and high quality. This thesis is based on a work to assist local manufacturing industries to optimise their production capability through the implementation of Group Technology (GT) concept. A computer program was developed based on Prof. Burbidge's Production Flow Analysis (PFA) method. Sample data for the machine-component grouping was obtained from a case study involving a machine shop. The computer program was used to form machine-part groupings. Initially the computer program formed five machine-part groupings. Later detailed study of the groupings resulted in three final cells. Group Analysis and Line Analysis studies were carried out on these cells to determine the number of machines of each type to be allocated in each machine group. Finally the proposed layout was simulated using WITNESS software to evaluate and justify the implementation of GT based Cellular Manufacturing (CM) cells on the selected case study.